Adsorptions of Sodium Ion/Atom on Graphene Quantum Dots for Battery Applications: A DFT Study - Mulya, Fadjar; Nugroho, Muhammad Adi; Kuamit, Thanawit; Setyawan, Dwi (Science and Technology Indonesia, 2025)
Sodium-ion batteries (SIBs) are emerging as a cost-effective and sustainable alternative to lithium-ion batteries, yet they face challenges such as lower energy density and electrode material instability. This study explores the potential of coronene and circumcoronene-based graphene quantum dots (GQDs) as anode materials for SIBs, focusing on three adsorption areas: central, intermediate, and edge, under two battery conditions: charging and discharging. By addressing these limitations through advanced nanostructuring, we employeddensityfunctional theory (DFT) withtheM06-2X/6-31G+(d)leveloftheorytoconductcomprehensive analyses of sodium adsorption on GQDs. Our findings reveal that both coronene and circumcoronene GQDs preferentially adsorb sodium at the edge areas due to the highest energy adsorption. In discharging conditions, coronene exhibited an adsorption energy of-1.09 kcal/mol, while circumcoronene showed-9.84 kcal/mol. In charging conditions, the adsorption energies were-33.44 kcal/mol for coronene and-37.19 kcal/mol for circumcoronene. Additionally, the energy gap of GQDs was significantly reduced after sodium adsorption, from 5.84 eV to 1.38 eV for coronene and from 4.33 eV to 1.63 eV for circumcoronene. Both GQDs showed theoretical voltages in the range of 1.40 to 1.47 V for coronene and 1.19 to 1.22 V for circumcoronene, respectively. Conclusively, our study recommends circumcoronene as large-sized GQDs as optimal SIB anode materials, offering higher adsorption energy, good conductivity, and reasonable electrochemical performance. This research addresses a theoretical gap by illuminating the impact of Na adsorption on GQDmolecular and electronic structures, aiding in the design of enhanced capacity nano-anodes for SIBs.